Mini review on Incorporation of Cotton Seed Meal, an Alternative to Fish Meal in Aquaculture Feeds - Pavan Kumar, Bokka; Ramudu, Kurva Raghu; Devi, B Chamundeswari (International Journal of Biological Research, 2014)
Fish nutrition has advanced dramatically in recent years with the development of new balanced commercial diets that promote best fish growth and health. Feed accounts for a major part (30-70%) of the total operation cost of an average fish farm. Traditionally, animal protein sources, particularly fishmeal have been the major ingredient of aqua feeds. Fishmeal is one of the most expensive ingredients in formulated fish feeds. Due to increasing demand, decreasing supply and the high cost of fish meal, fish nutritionists have concentrated their efforts to find alternative protein sources to substitute fish meal in the diet of fish. Thus, cottonseed meal (CSM), a by-product of the cotton fiber and cottonseed oil industries, may be used to replace fish meal partially or totally in fish diets. However, the cottonseed meal was evaluated by its anti-nutritional factors and its impact on the growth, survival, carcass composition and histopathology of fishes. It is observed that the more research is concentrated on the gossypol content in the cottonseed meal which is described as the anti-nutritional factor that shows high impact on the growth, carcass composition and pathological changes in the fish. Hence, considering these problems it is advised to use low levels of cottonseed meal in the aqua feeds. The gossypol level can be minimized by the solvent extracted cottonseed meal and be counteracted by the fortification of lysine and adding up of required iron levels. Further research may be required in histopathological studies to assess the toxicity levels in the tissues of the fish due to the gossypol factor. Keywords: Cotton Seed Meal, Fish Meal, Gossypol.